2006
DOI: 10.1038/sj.bjc.6603152
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishing blood and lymph vessel invasion in breast cancer: a prospective immunohistochemical study

Abstract: Recently, peritumoural (lympho)vascular invasion, assessed on haematoxylin -eosin (HE)-stained slides, was added to the St Gallen criteria for adjuvant treatment of patients with operable breast cancer (BC). New lymphatic endothelium-specific markers, such as D2-40, make it possible to distinguish between blood (BVI) and lymph vessel invasion (LVI). The aim of this prospective study was to quantify and compare BVI and LVI in a consecutive series of patients with BC. Three consecutive sections of all formalin-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
92
3
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(105 citation statements)
references
References 46 publications
8
92
3
2
Order By: Relevance
“…34,35 The distinction between lymph vessel and vascular invasion in breast cancer has also been demonstrated using D2-40 and the vascular marker CD34. 36 Furthermore D2-40 has been shown to be the best marker for lymphatic endothelium. 37 In this study, we identified lymph vessel invasion using D2-40 in 82/303 (27%) of cases of node negative breast cancer.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…34,35 The distinction between lymph vessel and vascular invasion in breast cancer has also been demonstrated using D2-40 and the vascular marker CD34. 36 Furthermore D2-40 has been shown to be the best marker for lymphatic endothelium. 37 In this study, we identified lymph vessel invasion using D2-40 in 82/303 (27%) of cases of node negative breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Van Eynden's study using D2-40 also showed that lymphovascular invasion was missed on H&E in 20%(peritumorally) and in 65% (intratumorally) of breast cancer cases. 36 The subgroup analysis of the 46 cases whose tumors were H&EÀ/D2-40 þ and the 36 cases that Endothelial lymphatic marker D2-40 A Arnaout-Alkarain et al…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2 Distinguishing between lymphatic vessels and blood capillaries is difficult using only hematoxylin and eosin (H&E) staining, and a commercially available D2-40 antibody reactive to podoplanin has been used to evaluate the lymphatic invasion of cancer in pathological examinations. 3 In addition, podoplanin was reported to be a useful marker for the diagnosis of vascular and non-vascular tumors of various organs. 4 Podoplanin was expressed by some vascular tumors with lymphatic differentiation, such as lymphangioma, Kaposi's sarcoma, Kaposiform hemangioendothelioma (socalled Dabska tumor), hobnail hemangioma, and a subset of angiosarcomas.…”
mentioning
confidence: 99%